Clinical Outcomes of Serious Infections due to Carbapenem-Resistant Enterobacteriaceae (CRE) in TANGO II, a Phase 3, Randomized, Multi-National, Open-Label Trial of Meropenem-Vaborbactam (M-V) Vs. Best Available Therapy (BAT). (4th October 2017) - Kaye, Keith S; Vazquez, Jose; Mathers, Amy; Daikos, George; Alexander, Elizabeth; Loutit, Jeffrey S; Zhang, Shu; Dudley, Michael N; Cornely, Oliver
Abstract: Background: Meropenem-vaborbactam (M-V) is a new β-lactam-β-lactamase inhibitor combination that restores the potency of meropenem in Klebsiella pneumoniae carbapenemase (KPC)-producing carbapenem-resistant Enterobacteriaceae (CRE). TANGO II is a randomized, open-label trial in patients with complicated urinary tract infection (cUTI), acute pyelonephritis (AP), hospital-acquired or ventilator-associated bacterial pneumonia (HABP/VABP), bacteremia, or complicated intra-abdominal infection (cIAI), due to known or suspected CRE. Clinical outcomes across indications in patients with documented CRE at baseline are presented. Methods: Subjects were randomized 2:1 to monotherapy with M-V (2g/2g every 8h as a 3h infusion) or Best Available Therapy (BAT) for 7–14 days. BAT included the following alone or in combination: carbapenems, aminoglycosides, polymyxin B, colistin, tigecycline or ceftazidime-avibactam (monotherapy only). Clinical cure was defined as a complete resolution of signs or symptoms such that no further antimicrobial therapy was required. Results: 72 patients were enrolled; 50 (69.4%) had a gram-negative baseline organism (m-MITT), and 43 (59.7%) had a baseline CRE (mCRE-MITT). Within mCRE-MITT, 20 patients had bacteremia, 15 had cUTI/AP, 5 had HABP/VABP, and 3 had cIAI. The most common baseline CRE pathogens were K. pneumoniae (86%) and Escherichia coli (7%). There was no consensus BAT regimen; however, combination therapy was used in 66.7% of cases. Treatment duration was similar across arms (mean 8.5 days for M-V and 8.1 days for BAT). Cure rates at end of treatment (EOT) and test of cure (TOC; 7 days after EOT) in mCRE-MITT and m-MITT populations are shown: Conclusion: M-V was associated with a higher rate of clinical cure at EOT and TOC than BAT across all indications in both m-MITT and mCRE-MITT populations. M-V is a promising new option for the treatment of CRE infections. Disclosures: K. S. Kaye, Xellia: Consultant, Consulting fee; Merck: Consultant and Grant Investigator, Consulting fee and Research support; The Medicines Company: Consultant and Grant Investigator, Consulting fee and Research support; G. Daikos, Achaogen: Consultant, Consulting fee; Rempex: Consultant, Consulting fee; Pfizer: Consultant, Research Contractor and Speaker's Bureau, Consulting fee, Research support and Speaker honorarium; E. Alexander, The Medicines Company: Shareholder, Salary; J. S. Loutit, The Medicine's Company: Employee and Shareholder, Salary; S. Zhang, The Medicines Company: Shareholder, Salary; M. N. Dudley, The Medicine's Company: Employee and Shareholder, Salary; O. Cornely, Archaogen: Consultant, Consulting fee; Anacor: Consultant, Consulting fee; Amplyx: Consultant, Consulting fee; Actelion: Consultant and Investigator, Consulting fee and Research grant; Astellas: Consultant, Investigator and Speaker's Bureau, Consulting fee, Research grant and Speaker honorarium; Basilea: Consultant, Investigator and Speaker's Bureau, Research grant; Cidara: Consultant and Investigator, Consulting fee and Research support; Da Volterra: Consultant, Consulting fee; F2G: Consultant and Investigator, Consulting fee and Research grant; Gilead: Consultant, Investigator and Speaker's Bureau, Consulting fee, Research grant and Speaker honorarium; Janssen: Consultant, Consulting fee; Matinas: Consultant, Consulting fee; Menarini: Consultant, Consulting fee; Merck/MSD: Consultant and Investigator, Consulting fee and Research support; Paratek: Consultant, Consulting fee; Scynexis: Consultant and Investigator, Consulting fee and Research grant; Seres: Consultant and Investigator, Consulting fee; Summit: Consultant, Consulting fee; Tetraphase: Consultant, Consulting fee; Vical: Consultant, Consulting fee; Aranis: Investigator, Research grant; AstraZeneca: Investigator, Research grant; Bayer: Research Contractor, Research grant; Duke University: Research Contractor, Research support; GSK: Investigator, Research grant; MedPace: Investigator, Research support; Melinta: Investigator, Research support; Miltenyi: Investigator, Research support; Pfizer: Investigator, Research support; Rempex: Investigator, Research support; Roche: Investigator, Research support; sanofi pasteur: Investigator, Research support; German Federal Ministry of Research and Education and the European Commission: Investigator, Research grant